Reflective Practice: Counseling Students’ Letters to Their Younger Selves in Practicum - Daniel A. DeCino; Phillip L. Waalkes; Joel Givens (Teaching and Supervision in Counseling, 2020)
In this reflective narrative study, we explored the stories of counselors-in-training at the end of their practicum courses. Thirty-six counselors-in-training (N= 36) engaged in reflective practice and wrote letters to their younger selves about their practicum experiences. Using a narrative-focused data analysis process, we created a thematic structure to retell the grand narrative of participants' practicum training experiences. Discussion and implications of this letter writing activity are offered to help understand how counselor educators can use reflective practices in their training courses.
Keywords: Reflective Practice; Letter Writing; Counselor Training